2002
DOI: 10.1080/00016480260000030
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Basic Fibroblast Growth Factor on Auditory Hair Cells after Noise Exposure

Abstract: The purpose of this study was to observe the protective effects of basic fibroblast growth factor (bFGF) on the cells of the inner ear using in vivo experiments. The studies were carried out using guinea pigs in which bFGF or artificial perilymph was perfused into the cochlea. The compound action potential (CAP) was measured before and after exposure to a sound simulating an explosion. The difference in CAP was significant between the bFGF-perfused group and the control group (p < 0.01, t = 3.896) and between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 31 publications
0
16
1
Order By: Relevance
“…Nerve growth factor (NGF), neurotrophin-3 (NT-3), brain-derived neurotrophic factor (BDNF), glial cell-derived neurotrophic factor (GDNF) and ciliary neurotrophic factor (CNTF) promote SGN survival in numbers similar to predeafened states, whether they are infused into the cochlea individually, in combinations of two or more, before ototoxic damage or after deafening [Ernfors et al, 1996;Gillespie et al, 2003Gillespie et al, , 2004Miller et al, 1997;Shah et al, 1995;Shinohara et al, 2002;Staecker et al, 1996;Wise et al, 2005;Ylikoski et al, 1998]. In addition, HCs can be protected from cell death if NT-3, GDNF or fibroblast growth factor (FGF) is applied prior to or up to 2 h after noise or ototoxic insult [Keithley et al, 1998;Kuang et al, 1999;Ruan et al, 1999;Shoji et al, 2000a, b;Sugahara et al, 2001;Yamasoba et al, 2001;Zhai et al, 2002]. Current data indicate that neurotro-…”
mentioning
confidence: 99%
“…Nerve growth factor (NGF), neurotrophin-3 (NT-3), brain-derived neurotrophic factor (BDNF), glial cell-derived neurotrophic factor (GDNF) and ciliary neurotrophic factor (CNTF) promote SGN survival in numbers similar to predeafened states, whether they are infused into the cochlea individually, in combinations of two or more, before ototoxic damage or after deafening [Ernfors et al, 1996;Gillespie et al, 2003Gillespie et al, , 2004Miller et al, 1997;Shah et al, 1995;Shinohara et al, 2002;Staecker et al, 1996;Wise et al, 2005;Ylikoski et al, 1998]. In addition, HCs can be protected from cell death if NT-3, GDNF or fibroblast growth factor (FGF) is applied prior to or up to 2 h after noise or ototoxic insult [Keithley et al, 1998;Kuang et al, 1999;Ruan et al, 1999;Shoji et al, 2000a, b;Sugahara et al, 2001;Yamasoba et al, 2001;Zhai et al, 2002]. Current data indicate that neurotro-…”
mentioning
confidence: 99%
“…(Zhai et al 2002; showed that this neurotrophic factor protects inner and outer hair cells from acoustic trauma and may facilitate the recovery of hearing. The neuroprotective effect of topically administered bFGF was also showed in injured cochlear nerve (Sekiya et al, 2003).…”
Section: Discussionmentioning
confidence: 98%
“…The presence of FGF receptors in the cochlea and their upregulation in the organ of Corti following an acoustic overstimulation (Pirvola et al, 1995) may underline the protective action of FGF-2 from glutamate/ aminoglycoside neurotoxicity, noise exposure, or injury of the cochlear nerve on cochlear neuronal and hair cell damage (Low et al, 1996;Zhai et al, 2002Zhai et al, , 2004Sekiya et al, 2003). It is also possible that FGF-2 may cooperate with other neurotrophic factors in its ability to promote trophism in the auditory system because the presence of nerve growth factor triggers neuritogenesis in the medium of cultured spiral ganglion neurons pretreated with bFGF (Lefebvre et al, 1991a,b).…”
Section: Discussionmentioning
confidence: 99%
“…KEY WORDS: auditory; basic fibroblast growth factor; FGF-2; cochlear nucleus; glial cell; immunohistochemistry; spiral ganglion; cochlea; 4-chloro-naphtol Many in vivo and in vitro experiments have demonstrated the role of neurotrophic factors in the auditory system (Lefebvere et al, 1991a,b;Ernfors et al, 1996). Particularly, the protective actions of the basic fibroblast growth factor (bFGF, FGF-2), a potent mitogenic protein that displays a large spectrum of actions during development and adult life (for review, see Gospodarowicz et al, 1987;Baird and Klagsbrun, 1991), have been extensively described in the auditory pathways (Low et al, 1996;Zhai et al, 2002Zhai et al, , 2004.For instance, in vitro and in vivo experiments demonstrated an increased survival of cultured spiral ganglion neurons, explanted from adult rats, in the presence of FGF-2 (Lefebvre et al, 1991b) and that the molecule was able to protect auditory neurons and hair cells of the organ of Corti from glutamate neurotoxicity and intense noise exposure (Zhai et al, 2004).FGF-2 immunoreactivity has been described in the cytoplasm of neurons and in the nuclei of glial cells widely distributed throughout the central nervous system (Matsuyama et al, 1992;Woodward et al, 1992;Chadi et al, 1993b;Fuxe et al, 1996). In the peripheral nervous system, FGF-2 immunoreactivity was found in the cytoplasm of neurons of the dorsal spinal root (Kato et al, 1992) and trigeminal (Okada et al, 1993) ganglia.…”
mentioning
confidence: 98%